Wavelength division multiplexing : a practical engineering guide - Grobe, Klaus (Wiley series in pure and applied optics, 2014)
"In this book, Optical Wavelength Division Multiplexing (WDM) is approached from a strictly practical and application-oriented point of view. Based on the characteristics and constraints of modern fiber-optic components, transport systems and fibers, the text provides relevant rules of thumb and practical hints for technology selection, WDM system and link dimensioning, and also for network-related aspects such as wavelength assignment and resilience mechanisms. Actual 10/40 Gb/s WDM systems are considered, and a preview of the upcoming 100 Gb/s systems and technologies for even higher bit rates is given as well.Key features: Considers WDM from ULH backbone (big picture view) down to PON access (micro view). Includes all major telecom and datacom applications. Provides the relevant background for state-of-the-art and next-gen systems. Offers practical guidelines for system / link engineering. "--